Antimicrobial Effect of Zn2+ Ions Governs the Microbial Quality of Donor Human Milk - Hutchings, Carmel; Prokocimer Yair, Zafnat; Reifen, Ram; Shemesh, Moshe (Foods, 2021)
Donor human milk (HM) obtained at HM banks is exceptionally crucial for the feeding and treatment of preterm infants. Bacterial contaminations of HM in various stages of its handling are very common and can lead to disqualification of donations or severe infections in worse cases. Hence, HM donations are subject to strict bacteriological evaluations pre- and post-pasteurization. The main contaminating species vary between countries, banks and donors and even exhibit inter-individual variation. We initiated an assessment of the bacteriological composition of HM donated by women hospitalized in a neonatal intensive care unit in Israel. The most common bacterium identified was Staphylococcus epidermidis, found in all but one of the HM samples; the presence of several species of coagulase-negative Staphylococci was also noted. Next, we sought to develop a platform towards antibacterial treatment using Zn2+ ions that have recently been found to be potent against contaminants isolated from bovine milk. Zn2+ efficiently inhibited the growth of viable aerobic population and S. epidermidis in HM. Growth was also inhibited in other Gram-positive bacteria such as Bacillus cereus, a well-known food-borne pathogen. S. epidermidis and B. cereus cells grown in the presence of zinc were taken for microscopic evaluation, aiming to demonstrate zinc’s antimicrobial mode of action morphologically. Images obtained using scanning electron microscopy indicated leakage of cellular content and cell lysis in S. epidermidis. Besides, B. cereus cells showed abnormalities in their cell surface and complete loss of flagella upon treatment with zinc. Along with the above findings, it should be noted that this was a pilot study that tested how high doses of Zn2+ affect breast milk as a product. Further research is likely needed on the safety of consumption of Zn2+-treated HM in infants and older children.